The expression of function g(x) is [tex](\frac x2 - 1)^2[/tex]
The function is given as:
[tex]f(x) = x^2[/tex]
When the function is shifted right by 1 unit, the rule is:
f'(x) = f(x - 1)
So, we have:
[tex]f(x) = (x - 1)^2[/tex]
When the function is compressed horizontally by a factor of 2, the rule is:
f'(x) = f(x/2)
So, we have:
[tex]g(x) = (\frac x2 - 1)^2[/tex]
Hence, the expression of function g(x) is [tex](\frac x2 - 1)^2[/tex]
Read more about function transformation at:
https://brainly.com/question/13810353
#SPJ1